anonymous
  • anonymous
http://gyazo.com/ecaceb89b3a014abf50e53dbeaebf4ef.png?1354481207 I can't get my head around this question. I've got that SR=PRtan35 and SR=QRtan40, which looks like it could help, but I can't figure it out. Please help? :)
Trigonometry
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
jim_thompson5910
  • jim_thompson5910
let h = height of pole sin(40) = h/QS QS*sin(40) = h QS = h/sin(40) sin(35) = h/PS PS*sin(35) = h PS = h/sin(35)
jim_thompson5910
  • jim_thompson5910
each triangle PRS and QRS are right triangles so we can say PR^2 + RS^2 = PS^2 PR^2 + h^2 = PS^2 PR^2 + h^2 = (h/sin(35))^2 --------------------- QR^2 + RS^2 = QS^2 QR^2 + h^2 = QS^2 QR^2 + h^2 = (h/sin(40))^2
jim_thompson5910
  • jim_thompson5910
Now use what you found SR=PRtan35 and SR=QRtan40 PRtan35 = QRtan40 PR = QR*tan(40)/tan(35)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

jim_thompson5910
  • jim_thompson5910
Since PR = QR*tan(40)/tan(35) we go from PR^2 + h^2 = (h/sin(35))^2 to ( QR*tan(40)/tan(35) )^2 + h^2 = (h/sin(35))^2 if you let x = QR and y = h, then we get this equation ( x*tan(40)/tan(35) )^2 + y^2 = (y/sin(35))^2
jim_thompson5910
  • jim_thompson5910
again, let x = QR and y = h to go from QR^2 + h^2 = (h/sin(40))^2 to x^2 + y^2 = (y/sin(40))^2
jim_thompson5910
  • jim_thompson5910
so you now have these 2 equations (with 2 unknowns) ( x*tan(40)/tan(35) )^2 + y^2 = (y/sin(35))^2 x^2 + y^2 = (y/sin(40))^2

Looking for something else?

Not the answer you are looking for? Search for more explanations.